Impaired inflammatory state of the endometrium: a multifaceted approach to endometrial inflammation. Current insights and future directions - Drizi, Amal; Djokovic, Dusan; Laganà, Antonio Simone; van Herendael, Bruno (Menopause Review/Przegląd Menopauzalny, 2020)
New insights into the complex and fine-regulated inflammatory mechanisms involved in the endometrium reveal multiple facets to the problem of endometrial inflammation. However, the entity termed chronic endometritis is to date restricted to infectious etiology and managed with antibiotics. Conversely, the concept of impaired inflammatory state of the endometrium (IISE) provides a more global approach to defective endometrial inflammation, considering both infectious and non-infectious etiology. A non-systematic review was done through a search on MEDLINE, EMBASE, Global Health, The Cochrane Library, Health Technology Assessment Database and Web of Science, research registers. Pertinent original and review articles, published in English or French until December 31, 2019, were selected. A compelling body of evidence demonstrates transient, repeated and persistent IISE to be a major factor of most problematic disorders in obstetrics/gynecology, such as endometrial polyps, unexplained infertility, miscarriage, placenta-related pathology and endometrial cancer. When scheduled accordingly, hysteroscopy can play a key role in the IISE assessment. Robust data suggests the pertinence of minimal-effective anti-inflammatory regimens for therapeutic IISE targeting. This review provides a comprehensive update on the multiple facets of inflammation in the endometrial physiology and pathology. Further research is needed to improve classification, diagnosis and treatment of IISE.